Analysis of critical thinking ability based on student gender through the implementation of independent curriculum in chemistry learning - Leony Sanga Lamsari Purba (Jurnal Pendidikan Kimia (JPKIM), 2022)
The implementation of the independent curriculum in high schools after the Covid-19 pandemic has become a challenge for teachers and education implementers because the demands of 21st century education must fulfill the 4C skills, one of which is critical thinking for male and female students. This research is a descriptive quantitative research, with a one group control posttest only research design, to analyze students' critical thinking skills in chemistry learning with an independent curriculum when viewed from gender differences. The population in this study is students senior high school in Jakarta, and the samples used in this study were 58 students consisting of 34 male students and 22 female students who were taken by random technique. Instrument test in this study was multiple choice questions consisting of 15 questions, which consisted of 3 sections according to Bloom's taxonomy, namely questions number 1-5 on C4, numbers 6-10 on C5 and numbers 11-15 on C6. The test instrument used is valid through the revision results according to the expert validator's input. The instruments used to obtain information regarding critical thinking skills were analyzed descriptively and the average male score was 56.67 (N=34), while for female it was 57.27 (N=22). Based on these data, the difference in critical thinking ability when viewed from gender differences is only 0.60 on a scale of 100 (Sig. <0.05). Furthermore, further test results show that there are differences in the critical thinking abilities of male and female students when learning chemistry in the independent curriculum.Keywords: Critical thinking; Chemistry; Curriculum; Gender